Mobile phone text messaging for improving the uptake of vaccinations: a systematic review protocol. Issue 8 (4th August 2014) - Kalan, Robyn; Wiysonge, Charles S; Ramafuthole, Tshepiso; Allie, Kurt; Ebrahim, Fatima; Engel, Mark Emmanuel
Abstract : Introduction: Low vaccine coverage is a major public health concern, the consequences of which contribute to around 1.5 million child deaths from vaccine-preventable diseases. Thus, innovative strategies to rapidly increase coverage and recall rates for vaccinations are urgently required. Mobile text messaging (or short messaging service, SMS) has the potential to help increase vaccination coverage and therefore we propose to conduct a review of the current best evidence for the use of SMS as an intervention to promote vaccination coverage. Methods and analysis: This article describes the protocol for a systematic review of the effectiveness of SMS in improving the uptake of vaccination. Primary and secondary outcomes of interest are prespecified. We will preferably include randomised controlled trials (RCTs). However, non-randomised studies (NRS) will be considered if there is an inadequate number of RCTs. We will search several bibliographic databases (eg, PubMed, EMBASE, CINAHL, CENTRAL, Science Citation Index, Africa-Wide Information and WHOLIS electronic databases and search sources for grey literature. Following data extraction and assessment of risk of bias, we will meta-analyse studies and conduct subgroup analyses, according to intervention subtypes. We will assess clinical heterogeneity and statistical heterogeneity. For outcomes without quantitative data, a descriptive analysis will be used. This review protocol is registered in the PROSPERO International Prospective Register of systematic reviews, registration number 2014:CRD42014007531 Ethics and dissemination: Ethics is not required for this study, given that this is a protocol for a systematic review, which uses published data. The findings of this study will be disseminated through peer-reviewed publications and conference presentations. We anticipate that the results could be used by researchers and policymakers to help inform them of the efficacy of mobile phone text messaging interventions to promote increased vaccination coverage. Trial registration number: PROSPERO registration number 2014:CRD42014007531.